Profound reductions in first and total cardiovascular events with icosapent ethyl in the REDUCE-IT trial: why these results usher in a new era in dyslipidaemia therapeutics - Boden, William E (Eur Heart J, 2020)
The aims of this clinical review are to: (i) highlight the importance of elevated baseline triglycerides (TG) in the setting of well-controlled low-density lipoprotein cholesterol (LDL-C) on statins as a major contributor to residual atherosclerotic cardiovascular disease (ASCVD) risk, particularly among patients with type 2 diabetes mellitus, metabolic syndrome, and obesity whose distinctive lipid phenotype cannot be optimally treated with LDL-C reduction therapy alone; (ii) describe the findings and clinical implications of the landmark REDUCE-IT trial in which ethyl eicosapentaenoic acid significantly improved ASCVD outcomes. While many genetic studies have shown that elevated TG are an independent causal factor for ASCVD, prior placebo-controlled trials using niacin, fibrates, omega-3 fatty acids, and dietary supplement fish oil preparations have failed to demonstrate significant CV event reduction when added to statin therapy. In contrast, the REDUCE-IT trial in 8179 participants showed convincingly that the administration of 4 g daily of icosapent ethyl (an ethyl ester of eicosapentaenoic acid) in patients at high risk for ASCVD with increased levels of baseline TG [median value, 2.44 mmol/L (216.0 mg/dL)] but well-controlled LDL-C [median value, 1.94 mmol/L (75.0 mg/dL)] reduced significantly incident events across both the trial primary endpoint and multiple prespecified secondary endpoints, including cardiovascular death, as well as both subsequent and total primary endpoint and key secondary endpoint events. Icosapent ethyl unequivocally contributed to ASCVD event reduction over and above statin therapy. The REDUCE-IT trial results should alter our approach to managing a growing population of hypertriglyceridaemic patients whose lipid phenotype requires more intensive treatment beyond LDL-C lowering alone.